Low Carbon e-Book on Climate Change with Education for Sustainable Development Framework for Sustainability Literacy of 7th Grader - Warliyah, Heli; Permanasari*, Anna; Rachman, Indriyani; Matsumoto, Toru (Jurnal IPA & Pembelajaran IPA, 2023)
Climate change and its impact on the environment is a topic that is aligned with low-carbon education principle to support the education for sustainable development framework. A low carbon e-book was developed to improve sustainability literacy. The e-book was then used in science learning and its effectiveness in improving sustainability literacy was investigated using a pre-experimental method with a pre-post-test design, with 40 grade 7 students of Junior High School in West Java-Indonesia as research subjects. The results showed that the developed e-book met the feasibility of the book in terms of content, presentation technique, grammar, graphics, and ease of use content validity ratio with qualified category, content validity index index with appropriate category. In addition, the book, which is presented with different examples of low-carbon education, is interesting for students because the illustrations are fun for students and the functions displayed are updated according to the character of students who are familiar with the IT world. The results show that learning with other e-books can improve students' sustainability literacy in the medium category